The impact of etnocontructivism in social affairs on pedagogic competencies - Syahrial Syahrial; Asrial Asrial; Dwi Agus Kurniawan; Faizal Chan; Ahmad Hariandi; Reza Aditya Pratama; Putut Nugroho; Retno Septiasari (International Journal of Evaluation and Research in Education (IJERE), 2019)
Teacher Competency Test is a test of mastery of professional and pedagogic competencies in the cognitive domain as a basis for establishing continuous professional development activities and part of teacher assessment. The test is a source and as a material for mapping the competencies that a teacher has regarding professional and pedagogical competence in an area. The low competence of the pedagogical field shows that teachers are not professional. Therefore the teacher will find it difficult to be able to provide a good pursuit of students. One way to improve the competence of teachers in pedagogic fields is by increasing teacher understanding and knowledge of local wisdom in learning. The essence of local and national cultural values in the education curriculum is now a bustling thing to be talked about by the people of Indonesia. Social ethnoconstructivism is able to be a solution amid the current developments and cultural shifts. This study wants to see how high the impact of ethnoconstuctivistic knowledge on teacher pedagogical competencies. In addition, age and gender are also separate discussions to see their influence on pedagogical competence. This research uses descriptive qualitative research. Samples in this study were elementary school teachers in three districts/cities in Jambi Province. The results show that teachers' ethnoconstructivism knowledge has an influence on the teacher's pedagogical competence. The age of a teacher also has an impact on pedagogical competence, but gender does not affect the teacher's pedagogical competency.